Scientific Evidence of Chinese Herbal Medicine (Gegen Qinlian Decoction) in the Treatment of Ulcerative Colitis - Jinke Huang; Jiaqi Zhang; Yifan Wang; Jing Ma; Xuefei Yang; Xiaoxue Guo; Mi Lv; Jinxin Ma; Yijun Zheng; Fengyun Wang; Xudong Tang (Gastroenterology Research and Practice)
Objectives. Gegen Qinlian decoction (GQD), a Chinese herbal compound, has been widely used in the treatment of ulcerative colitis (UC) in China. However, evidence from systematic reviews (SRs)/meta-analyses (MAs) of GQD in UC remains highly controversial. To collate, evaluate, and synthesize the current evidence, we carried out this study. Methods. SRs/MAs of GQD for UC were obtained from eight databases. Methodological Quality of Systematic Reviews 2 (AMSTAR-2) was utilized to appraise the methodological quality, Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) for reporting quality, and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) for evidence quality. Results. Four eligible SRs/MAs were obtained. According to AMSTAR 2, all SRs/MAs were graded as critically low quality. According to PRISMA checklist, all SRs/MAs failed to report the information of protocol and registration. With GRADE, no outcome measure with high-quality evidence was found, and the evidence quality for outcome measures was in the moderate to critically low levels. Conclusions. GQD with conventional medicine (CM) seems to be more effective in UC than CM alone. This finding provides a new alternative strategy for the treatment of UC. However, owing to the limitations of the evidence provided by the included SRs/MAs, this conclusion must be treated with caution.